Self-reported knowledge and difficulties towards palliative care among healthcare professionals in rural China: a cross-sectional study - Junwei Niu; Min Feng; Changhui Song; Hui Xie (BMC Palliative Care)
Abstract Background Palliative care (PC) in rural China remains underdeveloped, with limited specialized services and significant challenges for healthcare professionals. This study aimed to examine the difficulties in providing PC and their factors from the perspective of healthcare professionals in rural Henan province, China, where specific PC services are currently unavailable. Methods A cross-sectional study was conducted between June and July 2024, using a convenience sample of 255 healthcare professionals from four secondary/tertiary hospitals participated. Data were collected on participants’ demographic characteristics, information on recently deceased cancer patients they had cared for, and PC-related information. PC knowledge and PC difficulties were assessed using the Palliative Care Knowledge Questionnaire-Chinese version (PCKQ-PCN) and the Palliative Care Difficulties Scale (PCDS). Linear regression analysis identified factors associated with PC difficulties. Results Among the 255 participants (Mean[age]: 34.82 ± 7.04), 71.8% were females, 57.3% were physicians, and the average work experience was 10.20 years. Regarding PC experience, 48.2% had participated in 1–2 training sessions annually over the past two years, and 32.2% reported a poor understanding of PC. The total PCKQ-PCN mean score was 13.28 ± 2.62, with 25.2% of participants classified as having poor knowledge. The PCDS mean score was 42.58 ± 13.59. Linear regression analysis showed that participating in at least one PC training session every six months (β = -10.66; p = 0.032), having experience caring for seriously ill people at home (β =  -6.31; p = 0.024), greater knowledge of symptom management (β = -3.72; p = 0.012), and higher levels of basic knowledge (β = -5.12; p = 0.007) were negatively associated with PC difficulties. Conversely, limited understanding of PC (β = 12.95; p = 0.021), greater knowledge of spiritual care and death education (β = 4.95; p = 0.034), and having new rural cooperative medical insurance (β = 6.36; p = 0.023; β = 3.21; p = 0.042) were positively associated with PC difficulties. Conclusions This study highlights critical gaps in rural China’s PC services, including inadequate training, limited focus on spiritual needs and death education, and disparities in insurance coverage. Targeted training programs in healthcare professionals and policy reforms are urgently needed to improve PC quality and accessibility in rural areas.